The physiological effects of low-intensity neuromuscular electrical stimulation (NMES) on short-term recovery from supra-maximal exercise bouts in male triathletes - Malone, J. K.; Coughlan, G. F.; Crowe, L.; Gissane, G. C.; Caulfield, N. (European Journal of Applied Physiology, 2012)
This study investigated the acute effects of NMES on blood lactate (BLa) and performance parameters in trained male triathletes. On three separate days, 13 trained male triathletes performed six 30 s Wingate tests (30 WanT) on a cycle ergometer. Each session consisted of performing 3 × 30 WanT (bouts 1-3) followed by a randomly assigned 30 min recovery intervention of either: (i) passive (seated), (ii) active (cycling at 30% VO2max) or (iii) NMES (1 Hz/500 µs-ON:OFF 2:6 s). The 3 × 30 WanT bouts were then repeated (bouts 4-6) and compared to bouts 1-3 for peak power (PP), mean power (MP) and fatigue index (FI). BLa and heart rate (HR) were recorded at designated time points throughout. Data were analyzed using repeated measures ANOVA with Tukey`s honestly significant difference post hoc test. BLa decreased significantly faster during the active recovery intervention (P < 0.001), however, there were no significant differences between interventions for PP (P = 0.217), MP (P = 0.477) and FI (P = 0.234) when the post intervention bouts (4-6) where compared to the pre intervention bouts (1-3). NMES during recovery was not more effective than active or passive recovery for improving subsequent performance. Despite BLa clearing at a significantly faster rate for the active recovery intervention, PP, MP or FI did not improve significantly compared to NMES and passive. In conclusion, NMES does not appear to be more effective than traditional methods for enhancing short-term recovery from supra-maximal exercise bouts in trained male triathletes.